BETON MUTU TINGGI SCC( Self Compacting Concrete) UNTUK KONSTRUKSI BERKELANJUTAN - Fadhil Muhammad Nuryanto; Hanif Nanda Syahputra; Niza Widiana; Sigit Setyawan (Jurnal Teknik SILITEK, 2024)
The long time it takes for concrete to harden is a disadvantage of this material compared to other materials. Concrete is a material that is often used in infrastructure development. There are alternative construction materials where concrete can flow through the reinforcement and fill the entire space in the mould densely without any compaction assistance, namely SCC concrete. The purpose of this research, the manufacture of SCC concrete utilises industrial waste as a filler for cement replacement materials, namely Fly ash and Silica fume. By using American Concrete Instituted (ACI) mix planning and EFNARC standards, making 3 cylinders of concrete measuring 30 cm x 15 cm and with the design of adding fly ash (2%), silica fume (9%) in the Civil Engineering Laboratory of Universitas Muhammadiyah Surakarta, this addition can produce a compressive strength of 24 Mpa within 1 day exceeding the required compressive strength and can reduce the percentage of impact on the environment compared to conventional concrete by; cement (50.96%), fly ash (100%), silica fume (100%). The results of this research can reduce social impacts such as, helping in urgent construction such as roads, reducing noise effects, and of course also reducing project costs. The expenditure for making SCC concrete with fly ash and silica fume is quite economical at Rp. 1,624,517.25/m³. This research is expected to be a sustainable, easy, fast, efficient and economical concrete innovation but also high quality.